Development of nanotechnology in textiles - Haghi, A. K.; Zaikov, G. E. (Gennadiĭ Efremovich), 1935- (Nanotechnology science and technology series., 2012)
Nano textiles are those designed and engineered on the nanoscale to create specific functions. These nano functions are very diverse and range from UV protection and antibacterial functions to moisture management. This book summarizes the development of nanotechnology in textile areas.